Knowledge and lifestyle modifications for dyslipidaemia among patients on statins in Pretoria - Thandazile Z. September; John V. Ndimande; Henry I. Okonta; Carien Steyn; Tombo Bongongo (Journal of the Colleges of Medicine of South Africa)
Background: Nearly half of all non-communicable diseases are caused by cardiovascular diseases, for which one of the most important risk factors is dyslipidaemia. This study assessed the knowledge and lifestyle modification practices regarding dyslipidaemia among patients taking statins at Phedisong 4 Community Health Centre in Pretoria, South Africa.